2019
DOI: 10.1111/eea.12757
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial community associated with adult vine weevil (Otiorhynchus sulcatus) in UK populations growing on strawberry is dominated by Candidatus Nardonella

Abstract: Otiorhynchus sulcatus (Fabricius) (Coleoptera: Curculionidae), commonly known as black vine weevil or simply vine weevil, is an important pest of soft fruit and ornamental crops. This species is endemic to temperate areas of Europe but has spread to many other areas over the last century, including North America and Australasia. The ability of vine weevils to adapt to such different environments is difficult to reconcile with the parthenogenetic reproduction strategy, which is likely to underpin a low genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Infection with facultative (non-essential) endosymbiotic bacteria is widespread within herbivorous arthropod populations, including aphids (Luna et al, 2018), whiteflies (Ghosh et al, 2018), psyllids (Hansen et al, 2012), mites (Zhu et al, 2018) and weevils (Morera-Margarit et al, 2019). Many of these herbivorous arthropods are important agricultural and horticultural pests, and, therefore, understanding the effects of symbiont infection on arthropod fitness, arthropod pest status and the interactions between multiple trophic levels is a dynamic area of research (Oliver et al, 2014;McLean et al, 2016;Zytynska and Meyer, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Infection with facultative (non-essential) endosymbiotic bacteria is widespread within herbivorous arthropod populations, including aphids (Luna et al, 2018), whiteflies (Ghosh et al, 2018), psyllids (Hansen et al, 2012), mites (Zhu et al, 2018) and weevils (Morera-Margarit et al, 2019). Many of these herbivorous arthropods are important agricultural and horticultural pests, and, therefore, understanding the effects of symbiont infection on arthropod fitness, arthropod pest status and the interactions between multiple trophic levels is a dynamic area of research (Oliver et al, 2014;McLean et al, 2016;Zytynska and Meyer, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have revealed the presence of a core microbiota shared by populations of the same weevil species found at separate geographic locations. This is the case for the gut microbiota of the bark beetles Dendroctonus valens (Le Conte) and Dendroctonus mexicanus (Hopkins) in Mexico (Hernández‐García et al, 2018) and for the whole body microbiota of the vine weevil in the United Kingdom (Morera‐Margarit et al, 2019). For example, mountain pine beetles collected at separate locations shared a similar bacterial community.…”
Section: A Fast‐moving Field: High‐throughput Sequencing In the Studymentioning
confidence: 99%
“…To identify population diversity at a microbial level, Morera-Margarit et al (2019) characterised the bacterial community of vine weevils from various locations. The populations tested harboured very similar bacterial community compositions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of the newly developed bioinformatic pipeline QIIME2 could reveal greater between population variation in future investigations. Morera-Margarit et al (2019) used QIIME for the analysis of the vine weevil microbiota. This is an open-source bioinformatics pipeline for performing microbiome analysis from raw DNA sequencing.…”
Section: Introductionmentioning
confidence: 99%